The diagnostic value of GDF-15 for myocardial involvement in idiopathic inflammatory myopathy. (26th November 2020) - Qiu, Mengqian; Sun, Xiaoxuan; Qi, Xiaoqing; Liu, Xianfang; Zhang, Yue; Zhang, Ning; Lu, FengYun; Liu, Wangyan; Changjing, Feng; Wang, Qiang; Zhou, Lei
Abstract: Background: Cardiac involvement is a serious complication of idiopathic inflammatory myopathy (IIM). GDF-15 can predict the risk and the prognosis of cardiovascular disease, but its value is unclear in IIM. Objective: To investigate the diagnostic value of GDF-15 for myocardial involvement in IIM. Methods: A total of 77 IIM patients from May 2018 to August 2020 were included in this retrospective study. Of these, 43 patients underwent cardiac magnetic resonance (CMR) examination. There were 33 SLE patients and 16 healthy people were used as the control group. The concentration of GDF-15 of these groups was measured by ELISA. Results: There were significant differences in GDF-15 levels in patients with IIM, SLE and healthy controls (H = 45.291, P <0.001). GDF-15 levels were statistically significant different between IIM patients with the myocardial injury [1484.88(809.07 2835.50) pg/ml] and without myocardial injury [593.26(418.61 784.59) pg/ml, P =0.001]. After adjusted for age, renal function, the risk of myocardial injury in IIM patients increased an average of 0.3% by per increased unit of GDF-15 (odds ratio=1.003, 95% CI: 1.000, 1.007). The level of GDF-15 was positively correlated with extra-cellular volume (ECV) ( r s = 0.348, P =0.028). GDF-15 ≥ 929.505 pg/ml (area under the curve=0.856, 95% CI: 0.744, 0.968) predicted myocardial injury in IIM with a sensitivity of 0.75 and specificity of 0.90. Conclusion: GDF-15 could serve as a potential biomarker to predict myocardial injury in IIM patients.